2018
DOI: 10.1242/jcs.213876
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet consumption is functionally coupled to vacuole homeostasis independent of lipophagy

Abstract: Lipid droplets (LDs) store neutral lipids and are integrated into a cellular metabolic network that relies on functional coupling with various organelles. Factors mediating efficient coupling and mechanisms regulating them remain unknown. Here, we conducted a global screen in to identify genes required for the functional coupling of LDs and other organelles during LD consumption. We show that LD utilization during growth resumption is coupled to vacuole homeostasis. ESCRT-, V-ATPase- and vacuole protein sortin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 87 publications
1
26
0
Order By: Relevance
“…To determine whether TAG lipolysis is indeed required for the formation of DAG microdomains during growth resumption, we monitored the distribution of cytosolic DAG pools in cells lacking TAG lipases. Tgl3 is an LD‐associated lipase that mediates TAG lipolysis during re‐entry of growth in S. cerevisiae . It has been shown that in the absence of the vacuolar lipase Atg15 ( atg15 Δ), Tgl3 and another LD‐associated lipase, Tgl4, become hyperactive, leading to enhanced lipolysis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether TAG lipolysis is indeed required for the formation of DAG microdomains during growth resumption, we monitored the distribution of cytosolic DAG pools in cells lacking TAG lipases. Tgl3 is an LD‐associated lipase that mediates TAG lipolysis during re‐entry of growth in S. cerevisiae . It has been shown that in the absence of the vacuolar lipase Atg15 ( atg15 Δ), Tgl3 and another LD‐associated lipase, Tgl4, become hyperactive, leading to enhanced lipolysis .…”
Section: Resultsmentioning
confidence: 99%
“…Tgl3 is an LD-associated lipase that mediates TAG lipolysis during re-entry of growth in S. cerevisiae. 63 It has been shown that in the absence of the vacuolar lipase Atg15 (atg15Δ), Tgl3 and another LD-associated lipase, Tgl4, become hyperactive, leading to enhanced lipolysis. 64 In fact, vacuolar DAG microdomains were abundant in cells lacking Atg15, where Tgl3 and Tgl4 activity is enhanced ( Figure 2).…”
Section: Dag Microdomains Are Formed In the Yeast Vacuole During Grmentioning
confidence: 99%
“…A subset of ESCRT components function in other pathways inside the cell. These include lipid droplet consumption ( Ouahoud et al. , 2018 ), peroxisome scission ( Mast et al.…”
Section: Discussionmentioning
confidence: 99%
“…Such feedback mechanisms have not been considered here, but could be included in future studies. Similarly, transport and metabolism of sterols and other lipids can change throughout the yeast cell cycle, for example prior to and after diauxic shift or during growth resumption and in the stationary state [85, 86]. Also, steryl esters in LDs can be utilized by other pathways, such as by ingestion into the vacuole (the yeast lysosome) during starvation in a process called lipophagy [87, 88].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%